2020
DOI: 10.1016/j.devcel.2020.03.009
|View full text |Cite
|
Sign up to set email alerts
|

OsNSUN2-Mediated 5-Methylcytosine mRNA Modification Enhances Rice Adaptation to High Temperature

Abstract: Highlights d OsNSUN2 is the major mRNA m 5 C methyltransferase in rice d m 5 C regulates mRNA translation d m 5 C modulates chloroplast homeostasis d m 5 C enhances rice adaptation to high temperature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
106
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 95 publications
(128 reference statements)
4
106
0
1
Order By: Relevance
“…Owing to the high‐throughput sequencing technologies, m 5 C methylome has been profiled in multiple species and different distribution patterns have been identified. In plants (rice, Arabidopsis thaliana ) and mammalian cell/tissues (mouse, human), m 5 Cs are mainly located in coding sequence (CDS) region, and enriched around the translation initiation codon (Amort et al, 2017; Tang et al, 2020; Yang et al, 2017; Yang, Perrera, et al, 2019). A different distribution pattern was also reported in zebrafish embryo where the m 5 C sites were observed to be widely distributed along whole CDS region without any specific enrichment regions (Yang, Wang, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the high‐throughput sequencing technologies, m 5 C methylome has been profiled in multiple species and different distribution patterns have been identified. In plants (rice, Arabidopsis thaliana ) and mammalian cell/tissues (mouse, human), m 5 Cs are mainly located in coding sequence (CDS) region, and enriched around the translation initiation codon (Amort et al, 2017; Tang et al, 2020; Yang et al, 2017; Yang, Perrera, et al, 2019). A different distribution pattern was also reported in zebrafish embryo where the m 5 C sites were observed to be widely distributed along whole CDS region without any specific enrichment regions (Yang, Wang, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a large number of studies have revealed the multiple molecular functions of m 5 C in RNA processing, such as mRNA export (Yang et al, 2017), RNA stability (Chen, Li, et al, 2019; Gigova, Duggimpudi, Pollex, Schaefer, & Koš, 2014; Väre, Eruysal, Narendran, Sarachan, & Agris, 2017; Yang, Wang, et al, 2019), translation (Janin et al, 2019; Tuorto et al, 2012), and long‐distance RNA transport of plant (Yang, Perrera, et al, 2019). Besides, RNA m 5 C modification also plays a vital role in mitochondrial activity (Haag et al, 2016), stress response (Janin et al, 2019; Tang et al, 2020), gametogenesis and embryogenesis (Cui et al, 2017; Hussain, Tuorto, et al, 2013; Yang, Wang, et al, 2019), nerve and brain development (Flores et al, 2017), and multifarious tumorigenesis and migration (Chen, Li, et al, 2019; Liang, Lin, Du, Qiu, & Zhang, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Evidently, the alkbh6 mutants showed a lower survival rate than wild-type plants under drought or heat stress, but a higher survival rate than the wild-type under salt stress ( Figure 2 , Figure 3 and Figure 4 ), indicating that ALKBH6 mediates different roles in the Arabidopsis response to various abiotic stresses. The importance of RNA methylation in stress responses in plants has been demonstrated in only a few cases; OsNUSN2, an mRNA m 5 C methyltransferase in rice, was shown to regulate mRNA translation and maintain chloroplast function, which enhances rice adaptation to heat stress [ 44 ], and m 6 A methylation was associated with the stabilization of the transcripts encoding salt response proteins in response to salt stress [ 45 ]. Although we do not know the mechanistic role of ALKBH6 in stress responses, our current results together with these previous findings point to the crucial role of RNA methylation/demethylation in the response of plants to abiotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…While recently it has been reported that viral ncRNA level increased followed by the loss of m 5 C modification, which was mediated by the ablation of NSUN2 [53] . Latest studies in this year have related m 5 C modification with the regulation of the thermal adaptability in animal and plant cells by regulating the functions of tRNA and mRNA [54] , [55] . A well-described hydroxymethylcytosine (hm5C) modification in DNAs was also observed in RNAs, which is oxidized form of m 5 C exhibiting important physiological roles in drosophila [56] .…”
Section: Introductionmentioning
confidence: 99%